Analysis of High-Speed Train Braking Systems: Components, Braking Force, and Air Consumption - P Paryanto; Joga D Setiawan; Abduh B Adriathmaa; Akhmat Busori; Mulyadi s Harjono; Nur Cahyo (Departemen Teknik Mesin, Fakultas Teknik, Universitas Diponegoro, 2023)
Ensuring the accuracy of parameters involved in high-speed train braking is essential for passenger safety and efficient operation. To achieve this, it is crucial to verify the force values, input and output specifications of braking system devices, and ensure they align with the desired values. This can be accomplished through quantitative research, which involves collecting braking system data from the train manufacturing company and consulting the technical book provided by the braking system manufacturer. In this particular research, the braking system of the high-speed train under investigation is designed as a combination of regenerative and electro-pneumatic braking. The regenerative braking force, determined by the DC motor and control, amounts to 95.46 kN, enabling train to decelerate from 220 km/h to 90 km/h. Subsequently, the electro-pneumatic braking continues the regenerative braking, with a force value resulting from the calculation of the output value on devices of 296.4 kN, bringing train to a complete stop. The air demand required to supply the pneumatic components of braking devices as well as the air demand of other devices in train is 121.35 liters/min. This figure accounts for the pneumatic supply needed for braking system's proper functioning, along with other pneumatic-dependent devices present on train. To validate the proposed design, a simulation of train braking operations was conducted using the data obtained from the research. This simulation aims to evaluate the effectiveness and efficiency of high-speed train braking system design, providing valuable insights for further improvements and optimizations.